Performance of important cultivars of guava (Psidium guajava) under sloppy wasteland conditions of kaymore plateau of Madhya Pradesh - NEGI, R S; GAUTAM, U S; SINGH, RAJESH (The Indian Journal of Agricultural Sciences, 2014)
The guava (Psidium guajava L.) cultivar Sangam produced the highest fruits yield/plant followed by Lalit and Shweta. Fruit size and weight was also found maximum in these cultivars. The total soluble solids were recorded maximum in fruits of Shweta followed by Lalit and Sangam. Sugar-acid ratio a criteria for taste was found to be highest in Sangam (40.71) and Lucknow 49 (40.41). These values were statistically at par with values recorded in Shweta, Lalit and Allahabad Safeda cultivars. The cultivars Sangam, Shweta and Lalit had good growth and found to be the best in terms of yield and quality parameters. Thus, on the basis of preliminary evaluation, it can be concluded that the cultivars, Sangam Shweta, and Lalit performed better under sloppy wastelands conditions in comparison to other tested cultivars.